An Experimental Study of the Effect of Vortex Shedding on Solar Collector Performance - Kadim, Alaulddin Abdulqader (Al-Khwarizmi Engineering Journal, 2014)
In this work, the effect of vortex shedding on the solar collector performance of the parabolic trough solar collector (PTSC) was estimated experimentally. The effect of structure oscillations due to wind vortex shedding on solar collector performance degradation was estimated. The performance of PTSC is evaluated by using the useful heat gain and the thermal instantaneous efficiency. Experimental work to simulate the vortex shedding excitation was done. The useful heat gain and the thermal efficiency of the parabolic trough collector were calculated from experimental measurements with and without vortex loading. The prototype of the collector was fabricated for this purpose. The effect of vortex shedding at different operation conditions was examined. The variation of angles of attack and wind velocity leads to different values of vortex loading coefficients and shedding frequencies. The relation between the dynamic characteristics and solar collector performance was evaluated. The finite element method was used to estimate the dynamic characteristic of the solar collector in addition to experimental work to evaluate the relation between the dynamic behavior of the collector and its performance.